2008
DOI: 10.1071/he08045
|View full text |Cite
|
Sign up to set email alerts
|

Young people and sun safety: the role of attitudes, norms and control factors

Abstract: Findings indicate that future interventions should target young people's normative and control beliefs related to sun safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 11 publications
4
22
2
Order By: Relevance
“…Previous TPB studies investigating young Australians' sun‐safe decision making provide useful guidance for intervention development. Underlying beliefs have been found to be strong influences for young Australians' sun‐protective behaviour . Specifically, a study among young people ( M age = 14.6 y) showed significant differences in normative beliefs and control beliefs (especially facilitators) between sun protectors and nonsun protectors, suggesting that young people who engage in more sun‐safe behaviour perceive greater approval from referents and are more likely to believe that helpful factors (eg, user‐friendly sunscreen) will facilitate their sun‐safe actions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous TPB studies investigating young Australians' sun‐safe decision making provide useful guidance for intervention development. Underlying beliefs have been found to be strong influences for young Australians' sun‐protective behaviour . Specifically, a study among young people ( M age = 14.6 y) showed significant differences in normative beliefs and control beliefs (especially facilitators) between sun protectors and nonsun protectors, suggesting that young people who engage in more sun‐safe behaviour perceive greater approval from referents and are more likely to believe that helpful factors (eg, user‐friendly sunscreen) will facilitate their sun‐safe actions .…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Specifically, a study among young people (M age = 14.6 y) showed significant differences in normative beliefs and control beliefs (especially facilitators) between sun protectors and nonsun protectors, suggesting that young people who engage in more sun-safe behaviour perceive greater approval from referents and are more likely to believe that helpful factors (eg, user-friendly sunscreen) will facilitate their sun-safe actions. 7 In a pilot TPB-based intervention among teenagers, intervention participants reported stronger control (motivator) and normative beliefs towards sun safety compared with the control-group members that were associated with enhanced sun-safe actions. 8 This article evaluates a school-based intervention aiming to improve sun-protective behaviour in adolescents.…”
mentioning
confidence: 99%
“…b Each question had the stem: "every time I go in the sun for more than 10 minutes during the next week". c "Others reminding you to sun protect" was raised in previous research (e.g., Robinson et al, 2008;White et al, 2008) as both a potential barrier to and motivator for sun-safety behavioral performance.…”
Section: Construct # Items Scale Measuresmentioning
confidence: 96%
“…The present study, therefore, comprised a preliminary test of a TPB belief-based intervention. It was expected that adolescents exposed to a belief-based intervention targeting previously identified (e.g., Robinson et al, 2008;White et al, 2008) costs and benefits, important referents, and barriers and motivators would report a significant improvement in their beliefs, intentions, and behavior for sun-safety from pre-to post-intervention compared to those adolescents in the control condition. For all constructs except for control belief barriers (where a decrease was expected), a significant increase over time on responses for intervention as opposed to control participants was hypothesized.…”
mentioning
confidence: 97%
“…Most of the literature suggests that the effect of tanning on appearance, and the association of tanned appearance with beauty and success, is the primary motivation for sunbathing and indoor tanning. A recent study by Robinson and colleagues7 indicated a significant increase (12%) over the past several decades in the number of young adults who believe a person looks better with a tan. However, appearance motivations may not account for the entirety of these risk behaviors, and while interventions focusing on appearance have been helpful in reducing these behaviors, there could be additional factors that account for the higher rates of UV exposure and lower engagement in skin protection among adolescents and young adults.…”
Section: Introductionmentioning
confidence: 99%